Eurasia on the Move Interdisciplinary Approaches to a Dynamic Migration Region Marlene Laruelle and Caress Schenk, editors - Marlene Laruelle; Caress Schenk (My University, 2018)
This interdisciplinary collection explores migration flows within and from Eurasia, focusing on internal and cross-border labor movements, regional integration, and evolving migration regimes. It addresses themes such as visa‑free regimes, EAEU labor mobility, Soviet-era registration policies, remittances, and geopolitical bargaining over migrant mobility. The volume brings together empirical case studies and theoretical reflections by scholars involved in Astana’s 2017 conference organized by Nazarbayev University and the Central Asia Program.
Keywords: migration in Eurasia; labor mobility; post-Soviet regime; visa-free zone; Eurasian Economic Union; Central Asia migrations